Respuesta :
Answer:
-2
Step-by-step explanation:
8 (-2x + 1) = 30 - (-4 + 3x) Distribute
-16x + 8 = 30 + 4 - 3x Combine like terms
-16x + 8 = 34 - 3x Rearrange terms
-13x = 26 Divide by -13 on both sides
x = -2
The answer is x=-2
8(-2x+1=30-(-4+3x)
Distribute 8 through the parentheses
-16x+8=30-(-4+3x)
Add the number
-16x+8=34-3x
Move the variable to the left-hand side and change its sign
-16x+8+3x=34
Collect like terms
-13x=34-8
Divide both sides of the equation by -13
-13x/-13=26/-13
X=-2
8(-2x+1=30-(-4+3x)
Distribute 8 through the parentheses
-16x+8=30-(-4+3x)
Add the number
-16x+8=34-3x
Move the variable to the left-hand side and change its sign
-16x+8+3x=34
Collect like terms
-13x=34-8
Divide both sides of the equation by -13
-13x/-13=26/-13
X=-2